2017
DOI: 10.1186/s12882-017-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study to assess the evaluation of living related kidney donors and their outcomes following nephrectomy at Kenyatta National Hospital

Abstract: BackgroundKidney transplantation is the renal replacement therapy of choice for end stage renal disease. To ensure safety regular audit of the donation process is necessary. The aim of this study was to assess the evaluation of potential living related kidney donors and document their outcomes following nephrectomy.MethodsThis was a retrospective descriptive study involving all living related kidney donors seen at Kenyatta National Hospital (KNH) renal unit from 2010 to 2014.Upon approval by KNH/ERC, the recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The majority of donors being parents or spouses suggests a familial inclination toward organ donation. This aligns with other studies emphasizing the prevalence of first-degree relatives as donors [13][14][15]. Our study suggests that encouraging awareness among male spouses could further enhance organ donation rates, reflecting the need for targeted interventions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of donors being parents or spouses suggests a familial inclination toward organ donation. This aligns with other studies emphasizing the prevalence of first-degree relatives as donors [13][14][15]. Our study suggests that encouraging awareness among male spouses could further enhance organ donation rates, reflecting the need for targeted interventions.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the study observes a higher proportion of female donors, with a male-to-female ratio of 1:3.4. This gender distribution trend aligns with previous studies in Kerala [12] and Maharashtra [13], but is contrary to findings from Kenya [14], where the majority of the donors are males (61%). Our findings emphasize the need for increased awareness among male donors about organ donation.…”
Section: Discussionsupporting
confidence: 88%
“…Because of this, CTA is crucial in selecting the best donor kidney based on the vasculature. According to earlier research, CTA can accurately identify donor vessels 95% to 100% of the time (12). All CTA results in our investigation were in agreement with the results of the operations on the harvested kidneys.…”
Section: Discussionsupporting
confidence: 89%
“…It is technically simpler to transplant kidneys with one renal artery than kidneys with several renal arteries. Furthermore, compared to kidney transplantation involving transplantation of kidneys with more than one renal artery, the postoperative rates of complication and kidney loss are lower when transplanting kidneys with just one renal artery (11,12). For a successful graft nephrectomy, the surgeon must have precise preoperative knowledge of the donor's renal vasculature in order to lower the risk of vascular injury and decrease the time of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Van der Merwe & Heyns among 50 South Africans, the prevalence of complications was 10%, out of which renal vein reconstruction was 4%, and infection, urethral injury and acute gastritis were all 2% [34]. Meanwhile a 4-year retrospective study in Kenyatta National Hospital reported the prevalence of donor complication to be 7.14%, the distribution being pleural breach (3.57%), hemorrhage (2.38%) and peritoneal breach (1.19%) [35]. Factors significantly associated with increased risk of donor complications following nephrectomy are African-American race, hematologic and psychiatric conditions, older age, obesity, and pre-donation hypertension [33,36,37].…”
Section: Discussionmentioning
confidence: 98%